Optimization of DCM boost chopper performance controlled by optimal PIDF regulator for stand-alone PV system - Ella Nkouna Paul Lionnel; Arnaud Obono Biyobo; Paul Owoundi Etouke; Yves Paulin Dangwe Sounsoumou; Reagan Jean Jacques Molu; Serge Raoul Dzonde Naoussi (Solar Compass)
This paper proposes a Maximum Power Point Tracking (MPPT) strategy for a photovoltaic (PV) panel, combining the Perturb and Observe (P&O) technique, Particle Swarm Optimization (PSO), and an optimal Duty Cycle Modulation (DCM) circuit. The Boost chopper, regulated by a Proportional-Integral-Derivative controller with a first-order low-pass filter (PIDF), serves as an interface between the photovoltaic source (PV) and the load, maximizing the extraction of energy produced by the solar panel. The results obtained in virtual simulation in the MATLAB/Simulink environment are satisfactory: we observe in standard conditions, namely temperature T = 25 °C and solar irradiation of 1000W/m2, a response without overshoot, a zero static error, a system stability time of 0.32 s, 0.13 s and 0.15 s respectively for three respective load values ​​(R0 = 50 Ω, R01 = 37.5 Ω and R02 = 25 Ω) in steady state. In transient state, taking into account the variation in solar irradiation, it can be seen that despite the fluctuations, the system manages to remain stable, attesting to the robustness of the controller used. To control the DCM Boost chopper. The comparative study carried out with other MPPT techniques such as (VSS-P&O, MIC, FOCV, FSS-RBFA, VSS-RBFA, AFLC, PSO and CS) applied to conventional boost converters attests that the proposed new prototype offers quite satisfactory performances compared to the latter.